Efficacy of Different Irrigation Techniques in Removing Ledermix Paste from Simulated Root Canal Irregularities - Baxter, Steffi; Nickoll, Maja; Konietschke, Frank; Rödig, Tina (Iranian Endodontic Journal, 2019)
Introduction: Root discoloration is reported after using Ledermix paste for prevention of external inflammatory root resorption in traumatically injured teeth. Therefore, it seems necessary to remove Ledermix completely from the root canal prior to root canal filling. The aim of this study was to evaluate the efficacy of sodium hypochlorite or alcohol with or without passive ultrasonic irrigation in removing Ledermix from standardized grooves in coronal and apical root canal thirds. Methods and Materials: Root canals of ten extracted single-rooted teeth were prepared to size 35 and split longitudinally. Standardized grooves were cut in the coronal and apical part of the root canal and filled with Ledermix paste. The reassembled specimens were irrigated with 1% NaOCl or 80% alcohol delivered with a size 30 syringe or with an ultrasonic device. The amount of remaining Ledermix paste was evaluated by three calibrated observers under 30× magnification using a four-grade scoring system. The data was analysed with a nonparametric ANOVA-type method for longitudinal data in factorial experiments. Pairwise comparisons were adjusted by using the Bonferroni corrections (P=0.05). Results: For the coronal groove, no statistical difference between passive ultrasonic irrigation with NaOCl or alcohol was found (P=0.089). Irrigation with ultrasonically activated alcohol was significantly more effective than manual irrigation irrespective of the irrigant (P=0.0118). Ultrasonic activation of alcohol removed Ledermix paste significantly better from the apical groove than the other irrigation procedures (P<0.05). Conclusion: This in vitro study showed that ultrasonic activation of alcohol was the most effective irrigation technique for removal of Ledermix paste, especially in the apical third of the root canal. Keywords: Alcohol; Irrigation; Ledermix Paste; Passive Ultrasonic Irrigation; Ultrasonics